Concrete Incorporated With Optimum Percentages of Recycled Polyethylene Terephthalate (PET) Bottle Fiber - Shahidan, Shahiron (International Journal of Integrated Engineering, 2018)
Plastic solid waste generation increases every year with the current consumption habit prevalent in the society nowadays. The improper disposal of plastic has been a major concern to the environment as it is not easily degradable. The issue of environmental pollution caused by polyethylene terephthalates (PET) has been extensively discussed and the best solution proposed is recycling. Therefore, one of the potential means to the problem is to recycle PET in the construction industry as fiber concrete (FC). FC is a composite material resulting from the addition of fibers to ordinary concrete. The objective of this research is to determine the compressive strength, splitting tensile strength and also the optimum percentages of recycled PET fibers in ordinary concrete. In this study, straight and irregular recycled PET fibers were used. The fibers were simply cut from PET plastic bottles. The length and width of recycled PET fiber were fixed at 50 mm and 5 mm respectively. The chosen percentages were 0.5%, 1.0%, 1.5% and 2.0% of fiber. A water-cement ratio of 0.45 was accepted for all ranges. The tests that were conducted included the slump test, compressive strength test and splitting tensile strength test. The specimens were tested on day 7 and day 28 after the concrete was mixed. The results obtained from each test indicated that when the percentage of recycled PET fiber used increases, the values obtained from the slump test and compressive strength test decreases while the value obtained from the splitting tensile test increases